Peran Guru dalam Menerapkan Metode Demonstrasi dan Role Play untuk Meningkatkan Pemahaman Fiqih Tayamum - Bela Beliana (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2026)
Learning fiqh of tayamum plays an important role in helping students understand and practice Islamic worship correctly. However, many students still experience difficulties in understanding the procedures of tayamum and lack confidence in practicing it independently. This study aims to analyze the effectiveness of demonstration and role play methods in improving students’ understanding and practical skills in tayamum learning at MDTA Muhammad Iqbal Cimahi. This research employed a qualitative approach involving teachers and students as research subjects. Data were collected through observation, interviews, and documentation to obtain a comprehensive understanding of the learning process. The findings revealed that the application of demonstration and role play methods improved students’ comprehension of tayamum procedures, increased their participation during learning activities, and enhanced their confidence in practicing tayamum correctly. In addition, these methods created a more interactive and engaging learning environment that supported students’ cognitive and spiritual development. Therefore, the use of active learning methods is considered effective in strengthening fiqh learning and encouraging students to perform worship independently and responsibly.